The utility and effectiveness of an internal iliac artery balloon occlusion catheter in surgery for large cervical uterine fibroids - Hiroshi Kaneda; Yasuhisa Terao; Yuko Matsuda; Kazunari Fujino; Takafumi Ujihira; Soshi Kusunoki; Miki Kimura; Akihiko Shiraishi; Ryohei Kuwatsuru; Satoru Takeda (Elsevier, 2017)
Objective: Surgery for uterine cervical fibroids is difficult because of restricted surgical access and risks such as intraoperative bleeding or injury to other organs. The internal iliac artery balloon occlusion catheter (IIABOC) provides effective hemostasis for placenta previa and atonic hemorrhage, and is increasingly used in surgery for uterine fibroids for controlling intraoperative hemorrhage. We investigated the efficacy and safety of the IIABOC for controlling intraoperative bleeding in total abdominal hysterectomies (TAH) and abdominal myomectomies (AM) for large cervical fibroids. Material and methods: From 2007 to 2014, the IIABOC was used in 22 cases (12 for TAH and 10 for AM) in which cervical fibroids fully occupied the pelvic cavity. Intraoperative blood loss, operating time, sample weight, use of blood transfusion, and injury to other organs were assessed. Result: Mean blood loss, operative time, and sample weight in the IIABOC cases were 510 mL, 178 min, and 2550 g for TAH; and 727.5 mL, 157.5 min, and 1850 g for AM. Blood loss divided by sample weight in IIABOC cases was significantly lower than that in non-IIABOC cases during the same time period, for both TAH and AM. Allogeneic blood transfusion was not necessary, and complications of injury to other organs did not occur in any of the 22 cases. Conclusions: For large cervical fibroids with limited operating space, surgery was performed under bleeding control by occlusion of the internal iliac artery with an IIABOC. This technique enables control of hemorrhage and safe operative management in gynecological surgery.